WTO/DDA 협상타결이 인삼산업에 미치는 영향과 경쟁력 제고 방안 - 성명환 (한국농촌경제연구원, 2004)
A purpose of this study is to analyze impact of WTO/DDA agreement on Korea's ginseng industry, to suggest its developing direction, and to introduce alternatives for raising its competitiveness. Korea's ginseng production is expected to decrease to 11,940tons and import to increase to 4,054 tons under WTO/DDA agreement by 2013. In addition, a Korea's self sufficiency rate of ginseng will be decreased to 90.4% and a number of ginseng farming household to 15,729. WTO/DDA agreement will cause severe damage to Korea's ginseng industry, if there is no special program. Assuming a government carrying plan to reduce production cost and marketing margin which will result in increasing new farming area and promoting consumer's demand, ginseng production is expected to increase to 14,202 tons and farming area to 11,089 ha, but import will decrease to 3,213 tons. A number of ginseng farming household is expected to about 12,000 tons caused from decreased farming area due to aged farmer and increased scale of economy. Analyzing customers expected purchasing preference for fresh ginseng, "maintain current purchase level" is the highest of 63.1%, "increase purchase level" is 23.4%, but "decrease purchase" is only 3.3%. Ginseng consumption is expected to increase. Korea ginseng has relatively low price competitiveness comparing with Chinese ginseng and it is limited to reduce production cost with current small scale of production. Ginseng farming household should plant minimum 4ha to make net profit which is similar with average yearly income of urban worker. It is need to increase production scale more than 4ha. Korea ginseng has very low price competitiveness. Korea ginseng had been sold ten times higher in price than chinese ginseng and 3 to 8 times higher than American ginseng in Hongkong ginseng market, 2001. Korea ginseng export has been rapidly decreased for this reason. Average production cost for 4-yeared Korea ginseng was Korean thousand won 10,375/10a which was 4.7 times higher than Korean thousand won 2,213/10a of Chinese ginseng. Farmer price and wholesale price of Korea undried ginseng were also 2.85 times and 4.72 times higher than those of chinese ginseng, 2002. If a local market is expanded and tariff is lowered, there would be a potentiality to increase ginseng import. Therefore, reducing production cost, improving local marketing system, expanding producing infrastructure, and expanding export market for Korea ginseng against imported ginseng are key resolutions to improve Korea's ginseng industry. We propose to make existing government plans - including producing high quality ginseng, promoting market flow through improvement of marketing system, maintaining brand value of Korea ginseng in oversea market, providing ground for growing industry through constant researching, and consolidating related rules and laws - into total resolution to improve Korea's ginseng industry. We also propose to build ginseng traceability system, support clean ginseng production comples, develop ginseng cluster, introduce ginseng check-off system, improve ginseng product inspection system, construct Korea ginseng research institute, and consolidate related rules and administration system. Researcher: Myung-Hwan Sung, Dong-Phil Lee, Seung-Woo Ryu, Song-Soo Lim, Chul-Min Kim, Moon-Ho Park, Won-Jin Lee e-mail Address: mhsung@krei.re.kr
Keywords: WTO; DDA; 인삼; 인삼산업